The mind of a maker: a learning framework for a continuum of K-12 invention education - Scharon, Catherine J.; Phillips, Annalise; Jones-Davis, Dorothy (Frontiers in Education, 2024)
Invention Education offers an exciting combination of knowledge and skill-based learning that is intertwined with important social and emotional competencies, especially for youth engaged in structured programs. KID Museum in Bethesda, Maryland is an experiential museum and K-12 makerspace whose offerings include a suite of Invention Programs implemented though formal curricula, field trips, and out-of-school time opportunities. KID Museum's Mind of a Maker learning framework is a promising pedagogical model for conceptualizing the broad range of learning outcomes targeted in these programs. Through comparison to other frameworks developed separately but concurrently, the Mind of a Maker offers insights into the underlying values and learning theories that shape Invention Education and can contribute to a fieldwide understanding of this area of experiential learning. This article explores constructs that promote an inventive mindset that may be reproducible in other learning contexts, as well as the ways in which framework outcomes are integrated into the design, reach, and evaluation of KID Museum's Invention Programs.